O problemach, potrzebach i zadaniach uniwersyteckich jednostek metodycznych (głos w dyskusji) - Fiszbak, Jolanta (Dydaktyka Polonistyczna, 2019)
The author focuses on academic methodological units’ problems of teaching Polish language and its literature, as well as on the problems of Polish language subject at schools. She proves a strong dependence between the two, which results in their mutual either development or regress. Decline in importance of Polish language subject at schools had a negative influence on performance of academic methodologists. The author emphasises the need for proper cooperation between methodological units around Poland and presents how it should be conducted. She also introduces problems in which cooperating methodologists should be interested. The result of the cooperation shall be both reinstating didactics to its rank of science and enhancing the education level of Polish language at schools.